Monitoring the Dynamic Behavior of PCI Bridges Using Short Period Seismograph and CSI Bridge Modeling - Said Jalalul Akbar; Maizuar Maizuar; Khairullah Yusuf; Joni Arfiandi (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Bridges are a critical part of transport infrastructure networks for social activities and economics of human life. Dynamic analysis of bridge is very important to perform in order to ensure the ability of the bridge to withstand loads and maintain the sustainability of transport infrastructure. This paper presents a methodological framework for monitoring dynamic behavior of the bridge (e.g., natural frequencies, displacement time history) by using civil engineering micro-tremor technique and numerical modeling. The study was conducted at the Alue Raya Bridge located in Lhokseumawe City, Aceh Province, Indonesia. To capture the dynamic behavior of the bridge under traffic loading, the micro-tremor techniques, e.g., Short Period Seismograph (SPS) sensor was placed underneath the bridge at the mid span of the bridge girder. The obtained vibration data were processed using Geopsy software. A three dimensional (3D) model of the bridge was then developed by using CSI Bridge software. The modal analysis was conducted to obtain the modal natural frequencies of the bridge due to traffic loads. The natural frequency measurements using SPS were compared with the simulation results. Through analyzing the measured results, it was found that the natural frequency of the bridge is around 4,3275 Hz which is very close to those obtained from numerical modeling using CSI bridge software. The measured maximum vertical displacement of the bridge girders is below 5mm under normal traffic condition which is under the allowable serviceability limit state requirements of the bridge. The outcomes of this study could have the potential to enable maintenance and capital works decisions which are an important component of the sustainability of transport infrastructure.